Synthesis and Analytical Study of New Chelating Resin Containing Sulfadiazine Drug - Madher N. Abdulla (E-Journal of Chemistry)
A new chelating resin was prepared by mixing sulfadiazine drug and TMP (trimethylolphenol). It was polymerized by heating to 90 °C then it was post cured to 100 °C after that it was grinded. The chelating behavior was examined against Cu2+, Ni2+ using patch method in deferent conditions like treatment time and pH at room temperature. The resin show a good loading capacity toward Cu2+ (in treatment time = 3 h & pH=4) = 0.2174 mg ion / 100 mg resin and it show good loading capacity toward Ni2+ (in treatment time = 24 h & pH=4) = 0.14 mg ion / 100 mg resin.